Mapping of Flood Potential in Urban Areas in Kemuning District, Palembang City and its Surroundings - Edison, Edison; Usman, Arie Putra (Jurnal Indonesia Sosial Sains, 2025)
The objectives of this study are Analyzing land use and river networks in the Kemuning sub-district area, Analyzing areas that have the potential to be flooded in the Kemuning area, especially the Simpang Polda and Reja Pipeline Palembang, Analyzing the area of land use affected by the presence of flood inundation in the Simpang Polda area and its surroundings. This study uses survey and recapitulation methods of data collection obtained from secondary data from several agencies related to Floods and Watershed Flows in the Bendung River area, Kemuning District in Palembang City.  Land use maps and river network systems based on the results of the analysis still have swamps or open spaces so that they can be used for infiltration. The magnitude of the potential flood inundation can be seen from the map based on a field inventory with 14 inundation location points. Based on the calculation of the rainy season with a 2-year period, the condition of the river catchment area is still in a safe condition. will remain in the period 5,10,25,50,100 in the category of flood hazard. The land area based on the analysis affected by the flood is 845 ha or 8.45 km or 23% of the area of Kemuning sub-district of 36.97 km. Factors that affect the height of inundation or flooding in the upstream, middle and downstream, both land geography, land structure, and drainage system, are changes in land use from swamps to moderate housing.